Comprehensive Review on the Interactions of Clay Minerals With Animal Physiology and Production - Damato, Anna; Vianello, Fabio; Novelli, Enrico; Balzan, Stefania; Gianesella, Matteo; Giaretta, Elisa; Gabai, Gianfranco (Frontiers in Veterinary Science, 2022)
Clay minerals are naturally occurring rock and soil materials primarily composed of fine-grained aluminosilicate minerals, characterized by high hygroscopicity. In animal production, clays are often mixed with feed and, due to their high binding capacity toward organic molecules, used to limit animal absorption of feed contaminants, such as mycotoxins and other toxicants. Binding capacity of clays is not specific and these minerals can form complexes with different compounds, such as nutrients and pharmaceuticals, thus possibly affecting the intestinal absorption of important substances. Indeed, clays cannot be considered a completely inert feed additive, as they can interfere with gastro-intestinal (GI) metabolism, with possible consequences on animal physiology. Moreover, clays may contain impurities, constituted of inorganic micronutrients and/or toxic trace elements, and their ingestion can affect animal health. Furthermore, clays may also have effects on the GI mucosa, possibly modifying nutrient digestibility and animal microbiome. Finally, clays may directly interact with GI cells and, depending on their mineral grain size, shape, superficial charge and hydrophilicity, can elicit an inflammatory response. As in the near future due to climate change the presence of mycotoxins in feedstuffs will probably become a major problem, the use of clays in feedstuff, given their physical-chemical properties, low cost, apparent low toxicity and eco-compatibility, is expected to increase. The present review focuses on the characteristics and properties of clays as feed additives, evidencing pros and cons. Aims of future studies are suggested, evidencing that, in particular, possible interferences of these minerals with animal microbiome, nutrient absorption and drug delivery should be assessed. Finally, the fate of clay particles during their transit within the GI system and their long-term administration/accumulation should be clarified.